Birokrasi Indonesia: Perspektif Teoritik dan Pengalaman Empirik - Suwarno Suwarno (Universitas Islam Indonesia, 2008)
In the era of reformation, leading to the establishment of a democratic civil society, it isnecessary to reduce the role and power of bureaucracy that was previously predominant.The bureaucracy should be politically kept neutral, and strictly supervised by society alone,through for examples non governmental organizations, press, and their representativeselected through general election which is trustworthy and fair. Their lack of performanceand their high pathology of corruption, collusion and nepotism should also be upgraded inorder to be in conformity with a political life of Indonesia which is more democratic, open,and transparent, in line with the spirit of reformation.Keywords: reformation, bureaucracy, reduce, upgraded